Screening Of Acid Translators On Lansia In The Puskesmas Stabat Kabupaten Langkat - Parinduri, Junaidi; Rusmini, Rusmini (Sean Institute, 2024)
Gout is a metabolic disease characterized by the buildup of uric acid that causes pain in the joints, very often found in the upper legs, ankles and middle legs. Gout is a disease called gout which is associated with a genetic effect on purine metabolism and can cause inflammation due to deposits of uric acid crystals in the joints of the fingers.This type of research is descriptive, that is, it provides an overview of uric acid levels in the elderly who seek treatment at the Stabat Public Health Center, Langkat Regency and is carried out from Oktober to November 2022. The population is all elderly patients who seek treatment at the Stabat Health Center, and the sample of this study was 60 people. The method of data collection is by using primary data obtained directly from the results of measurements of uric acid levels and then presented in tabular form to determine normal and abnormal conditions.The results showed that from a sample of 60 elderly people, uric acid levels increased by 40 people (67 %), while normal glucose levels were 20 people (33 %) and to improve the health of the elderly it is necessary to avoid consuming excessive food. containing high uric acid, perform regular physical activity and check blood uric acid levels regularly.